A biochemical, theoretical and immunohistochemical study comparing the therapeutic efficacy of curcumin and taurine on T-2 toxin induced hepatotoxicity in rats - Al-Zahrani, Maryam H.; Balgoon, Maha J.; El-Sawi, Nagwa M.; Alshubaily, Fawzia A.; Jambi, Ebtihaj J.; Khojah, Sohair M.; Baljoon, Raghad S.; Alkhattabi, Nuha A.; Baz, Lina A.; Alharbi, Asmaa A.; Ahmed, Amira M.; Abo elkhair, Ayat M.; et al. (Frontiers in Molecular Biosciences, 2023)
Introduction: Foodborne trichothecene T-2 Toxin, is a highly toxic metabolite produced by Fusarium species contaminating animal and human food, causing multiple organ failure and health hazards. T-2 toxins induce hepatotoxicity via oxidative stress causing hepatocytes cytotoxicity and genotoxicity. In this study, curcumin and taurine were investigated and compared as antioxidants against T-2-provoked hepatotoxicity. Methods: Wistar rats were administrated T-2 toxin sublethal oral dose (0.1 mg/kg) for 2 months, followed by curcumin (80 mg/kg) and taurine (50 mg/kg) for 3 weeks. Biochemical assessment of liver enzymes, lipid profiles, thiobarbituric acid reactive substances (TBARs), AFU, TNF-α, total glutathione, molecular docking, histological and immunohistochemical markers for anti-transforming growth factor-β1 (TGFβ1), double-strand DNA damage (H2AX), regeneration (KI67) and apoptosis (Active caspase3) were done. Results and Discussion: Compared to T-2 toxin, curcumin and taurine treatment significantly ameliorated hepatoxicity as; hemoglobin, hematocrit and glutathione, hepatic glycogen, and KI-67 immune-reactive hepatocytes were significantly increased. Although, liver enzymes, inflammation, fibrosis, TGFβ1 immunoexpressing and H2AX and active caspase 3 positive hepatocytes were significantly decreased. Noteworthy, curcumin’s therapeutic effect was superior to taurine by histomorphometry parameters. Furthermore, molecular docking of the structural influence of curcumin and taurine on the DNA sequence showed curcumin’s higher binding affinity than taurine. Conclusion: Both curcumin and taurine ameliorated T-2 induced hepatotoxicity as strong antioxidative agents with more effectiveness for curcumin.